Serial Imaging of Virus-Associated Necrotizing Disseminated Acute Leukoencephalopathy (VANDAL) in COVID-19 - Agarwal, S.; Conway, J.; Nguyen, V.; Dogra, S.; Krieger, P.; Zagzag, D.; Lewis, A.; Melmed, K.; Galetta, S.; Jain, R. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Various patterns of leukoencephalopathy have been described in coronavirus disease 2019 (COVID-19). In this article, we aimed to describe the clinical and imaging features of acute disseminated leukoencephalopathy in critically ill patients with COVID-19 and the imaging evolution during a short-term follow-up.MATERIALS AND METHODS: We identified and reviewed the clinical data, laboratory results, imaging findings, and outcomes for 8 critically ill patients with COVID-19 with acute disseminated leukoencephalopathy.RESULTS: All patients demonstrated multiple areas of white matter changes in both cerebral hemispheres; 87.5% (7/8) of patients had a posterior predilection. Four patients (50%) had short-term follow-up imaging within a median of 17 days after the first MR imaging; they developed brain atrophy, and their white matter lesions evolved into necrotizing cystic cavitations. All (8/8) patients had inflammatory cytokine release syndrome as demonstrated by elevated interleukin-6, D-dimer, lactate dehydrogenase, erythrocyte sedimentation rate, C-reactive protein, and ferritin levels. Most (7/8; 87.5%) patients were on prolonged ventilator support (median, 44.5 days; interquartile range, 20.5 days). These patients had poor functional outcomes (6/8 [75%] patients were discharged with mRS 5) and high mortality (2/8, 25%).CONCLUSIONS: Critically ill patients with COVID-19 can develop acute disseminated leukoencephalopathy that evolves into cystic degeneration of white matter lesions with brain atrophy during a short period, which we dubbed virus-associated necrotizing disseminated acute leukoencephalopathy. This may be the result of COVID-19-related endothelial injury, cytokine storm, or thrombotic microangiopathy.ADEMacute disseminated encephalomyelitisARDSacute respiratory distress syndromeCRPC-reactive proteinCOVID-19coronavirus disease 2019ESRerythrocyte sedimentation rateGCSGlasgow Coma ScaleIL-6interleukin-6INRinternational normalized ratioIQRinterquartile rangeLDHlactate dehydrogenasePRESposterior reversible encephalopathy syndromeSARS-CoV-2Severe Acute Respiratory Syndrome coronavirus 2VANDALVirus Associated Necrotizing Disseminated Acute LeukoencephalopathyWMwhite matter